Structural dynamics of PRR FLS2, PAMP flg22 and mutated co-receptor BAK1 of Arabidopsis thaliana - Nowrid, Nazia (Brac University, 2021)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.